Handbook of Practical Nematology - Harish K, Bajaj; Kanwar R.S (Jodhpur Scientific, 2011)
This book described the most commenly used methods on basic and applied aspects of nematology
Cuticle Conus Tylenchids Basiria
Keywords: Cuticle, Conus, Tylenchids